Audel pipefitter's and welder's pocket manual - McConnell, Charles (Wiley, 2003)
This little book is big on answersWhether you're an apprentice in the piping trades or a seasoned tradesperson, you'll find this completely revised and updated guide has answers to the questions you'll encounter on the job. Get current, concise facts on* Metrics and conversions* Tungsten inert gas welding and arc welding* Steam heating, hot water, refrigeration, and air conditioning systems* Grooved end/plain end piping systems* Process piping using plastics* Automatic fire protection systems* Terms, BTU fuel values, abbreviations, angle calculations,